Preservasi naskah kuno Gandoang melalui kegiatan digitisasi - Ute Lies Siti Khadijah; Lutfi Khoerunnisa; Elnovani Lusiana; Rully Khairul Anwar (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. Ancient manuscripts are one of the nation's many cultural heritages with historical significance. As a result, conservation measures must be implemented, one of which is the transfer of digital media. The purpose of this study is to learn about the efforts made to transfer Gandoang ancient manuscripts to Ciamis. Data Collection Methods. This study employs a qualitative case study approach, with data collected through observation techniques and semi-structured interviews with three informants. Data Analysis. Through Miles and Hubberman data analysis techniques; researchers organize, organize, and categorize them. Result and Discussion. The findings of this study indicate that, as part of the management's effort to preserve the Gandoang ancient manuscripts in collaboration with Tapak Karuhun Nusantara Foundation, converting them into a digital form into an e-book can be considered effective and efficient. The ancient manuscripts in this fragile state can now be preserved, allowing their existence to be used for a long time. Conclusion. Because of the internet, which allows everyone to read it wherever and whenever they want, the Gandoang e-book has proven to be more popular in the public. However, many ancient manuscripts in the Ciamis still require the attention of various parties due to their endangered state.